SEORANG WANITA DENGAN URTIKARIA KRONIK IDIOPATIK - Suryana, Ketut; Suastika Adiguna, Made (journal of internal medicine; Vol. 7, No. 2 Mei 2006)
Urticaria is characterized by red edematous plaques surrounded by a clear or red halo. The lesions are round or oval and may become polycyclic when confluent. They usually multiple and vary from 1 mm to several centimeters in diameter. They can occur at any site of the body and are typically associated with itching and sometimes burning. Skin returns to its normal appearances usually within 1-24 hours. Urticaria is sometimes accompanied by angioedema, in which the edematous process extends into the deep dermis and / or subcutaneous tissues. While patient with urticaria usually have symptoms confined to the skin they may have concomitant systemic manifestations. Urticaria is termed acute when episode less than 6 weeks, it’s termed chronic when episode persist longer. Chronic urticaria / angioedema, the syndrome last and average of 3-5 years, with 20% patients still symptomatic at 40 years. The syndrome is frustrating to patient and clinician alike in death a search for an exogenous cause is futile in the majority of patients. However in recent year its has been demonstrated that many patients involved idiopathic chronic urticaria (80% of the chronic type urticaria). The incidence of idiopathic chronic urticaria was 3% population. The diagnosis, there is no the specific approach. Mostly based on clinical history and several laboratory procedure and in certain condition need skin biopsy. The management; allergen avoidance, medicamentosa symptomatically. The first line; non sedating second-generation AH-1 and in a several case add by antihistamine AH-2. in severe case sometimes need the corticosteroids or another immunosuppressive.
Keywords: idiopathic chronic urticaria